2002
DOI: 10.1002/jnr.10421
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor‐α and neural circuits to the spinal cord during pregnancy

Abstract: Estrogen receptor immunoreactivity and mRNAs are present in spinal cord neurons in locations that are associated with sensory and autonomic innervation of female reproductive organs. The present study was undertaken to examine the expression of estrogen receptor-alpha in the spinal cord during different stages of pregnancy and to determine whether estrogen receptor-alpha-expressing neurons are related to uterine afferent nerves bringing information to the spinal cord at parturition. Immunohistochemistry showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 66 publications
(101 reference statements)
0
13
0
1
Order By: Relevance
“…Estrogen receptors are found throughout the central and peripheral nervous systems. In the peripheral nervous system, estrogen receptors are found in the spinal cord [12][13][14][15], dorsal root ganglia [16][17][18][19], autonomic pelvic ganglia [14,15], sympathetic ganglia [20,21], and Schwann cells [22]. Numerous studies have shown that estrogens affect the nervous system via both genomic and non-genomic mechanisms, including the development, proliferation, and regeneration of neuronal cells, gene expression, energy metabolism, hormone sensitivity, and the biosynthesis of structural proteins and enzymes [12,15,17,19,23].…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen receptors are found throughout the central and peripheral nervous systems. In the peripheral nervous system, estrogen receptors are found in the spinal cord [12][13][14][15], dorsal root ganglia [16][17][18][19], autonomic pelvic ganglia [14,15], sympathetic ganglia [20,21], and Schwann cells [22]. Numerous studies have shown that estrogens affect the nervous system via both genomic and non-genomic mechanisms, including the development, proliferation, and regeneration of neuronal cells, gene expression, energy metabolism, hormone sensitivity, and the biosynthesis of structural proteins and enzymes [12,15,17,19,23].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that ER α and to a lesser extent ER β are present in neurons of the spinal cord dorsal horn (Papka et al, 2001; Gintzler et al, 2008) in areas that topographically correspond to the distribution of central processes of visceral primary afferent neurons (Papka et al, 2002; Vanderhorst et al, 2009). These areas also express opioid receptors, which localize to pre-synaptic terminals of primary sensory neurons as well as to their postsynaptic targets in laminae I and II (Kline and Wiley, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Also, significant reduction in the number of neurons displaying p75 protein has been observed at the end of pregnancy, when estrogen levels are increased [42]. Moreover, considering the expression of ERs by neurons in autonomic and sensory areas of the lumbosacral spinal cord that have connections with female reproductive system [43], it is possible that the reduction in the number of postganglionic neurons found in the present study may partly result from changes of the density of ERs receptors on preganglionic neurons in response to E2 treatment, which could ultimately affect both the morphology and activity of these cells and consequently disturb the neuronal network function.…”
Section: Discussionmentioning
confidence: 99%